Destroying and Restoring Critical Habitats of Endangered Killer Whales. (1st September 2021) - Williams, Rob; Ashe, Erin; Broadhurst, Ginny; Jasny, Michael; Tuytel, Dyna; Venton, Margot; Ragen, Tim
Abstract: Endangered species legislation in the United States and Canada aims to prevent extinction of species, in part by designating and protecting critical habitats essential to ensure survival and recovery. These strict laws prohibit adverse modification or destruction of critical habitat, respectively. Defining thresholds for such effects is challenging, especially for wholly aquatic taxa. Destruction of critical habitat (e.g., prey reduction and ocean noise) threatens the survival and recovery of the 75 members of the endangered southern resident killer whale population found in transboundary (Canada–United States) Pacific waters. The population's dynamics are now driven largely by the cumulative effects of prey limitation (e.g., the endangered Chinook salmon), anthropogenic noise and disturbance (e.g., reducing prey accessibility), and toxic contaminants, which are all forms of habitat degradation. It is difficult to define a single threshold beyond which habitat degradation becomes destruction, but multiple lines of evidence suggest that line may have been crossed already.